2001
DOI: 10.2172/791184
|View full text |Cite
|
Sign up to set email alerts
|

Field surveys of office equipment operating patterns

Abstract: This paper presents the results of 11 after-hours walk-throughs of offices in the San Francisco CA and Washington D.C. areas. The primary purpose of these walk-throughs was to collect data on turn-off rates for various types of office equipment (computers, monitors, printers, fax machines, copiers, and multifunction products). Each piece of equipment observed was recorded and its power status noted (e.g. on, off, low power). Whenever possible, we also recorded whether power management was enabled on the equipm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 6 publications
2
35
2
Order By: Relevance
“…However, some studies e.g. [24][25][26] show that more than 50% of occupants leave their computers on when leaving a space. In order to address this concern, Milenkovic and Amft [27] proposed a dual technology occupancy detection system that combined PIR sensors and plug monitors for different equipment.…”
Section: Wired Network-based and Energy-related Solutionsmentioning
confidence: 99%
“…However, some studies e.g. [24][25][26] show that more than 50% of occupants leave their computers on when leaving a space. In order to address this concern, Milenkovic and Amft [27] proposed a dual technology occupancy detection system that combined PIR sensors and plug monitors for different equipment.…”
Section: Wired Network-based and Energy-related Solutionsmentioning
confidence: 99%
“…ENERGY STAR imaging equipment must meet either a maximum total energy consumption (TEC) We model residential and office settings separately due to different usage patterns. Commercial operating patterns are derived from equipment audits at various locations that provide time spent in each operating mode, nighttime turn-off rates, and power management success rates (Piette et al 1995;Nordman et al 1998;Webber et al 2001;Roberson et al 2004). Operating patterns for residential computers are derived from hours-of-use monitoring for a large sample of residential computer users (Media Metrix 2001).…”
Section: Office Equipmentmentioning
confidence: 99%
“…Additionally many office workers don't power down equipment at the end of the working day (Berl & de Meer 2011) and even fewer unplug equipment that may still draw power when turned off. A US field survey of office equipment operating patterns (Webber et al 2001) found that only 44% of computers and 32% of monitors where turned off at night, a similar UK based study (Zhang et al 2011) found that 60% of occupants don't power down at night time, with 31% powering down just occasionally and only 9% powering down regularly. Comparison of these two studies would seem to suggest that organisational or cultural background may have an influence on the rate of power down and reinforces the view that small power consumption patterns are generally not fully understood but offer significant potential for savings.…”
Section: Introductionmentioning
confidence: 98%
“…Conversely increased processing power and range of equipment utilised has resulted in predictions that small power will continue to have a significant impact (Jenkins, Singh & Eames, 2009) and that energy consumption associated with office eqiupment will continue to grow globally in the near future. (Webber et al 2001& Vereecken et al 2010 As noted by Junnila (2007) few studies have focused on quantifying the enduser influence on energy consumption, furthermore most energy managers believe end users influence to be minimal (Lukas, 2000). However it has previously been established that energy use of desktop equipment is highly influenced by occupant behaviour and is flexible in nature (Zhang, Siebers & Aickelin, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation